Contested illnesses : citizens, science, and health social movements - Brown, Phil; Morello-Frosch, Rachel; Zavestoski, Stephen (University of California Press, 2012)
"The politics and science of health and disease remain contested terrain among scientists, health practitioners, policy makers, industry, communities, and the public. Stakeholders in disputes about illnesses or conditions disagree over their fundamental causes as well as how they should be treated and prevented. This thought-provoking book crosses disciplinary boundaries by engaging with both public health policy and social science, asserting that science, activism, and policy are not separate issues and showing how the contribution of environmental factors in disease is often overlooked"--Provided by publisher.